Impact of Electromagnetic Interference Filter Performance in a System without and with Grounding for Supporting the Nanogrid Road Lighting System - Chaiyan Jettanasen; Sulee Bunjongjit; Atthapol Ngaopitakkul (My University, 2021)
This study focuses on the comparison of conducted electromagnetic interference (EMI) mitigation for a nanogrid road lighting system, using a passive EMI filter between ungrounded and grounded systems. An inverter was used as the equipment under test in the experiment. The inverter is a power conversion device that receives power from the source and supplies power to the AC electrical load of an LED luminaire. There are two points where the self-generated noises propagate to other nearby devices/equipment. For this reason, this study shows the EMI spectrum from both the DC input and AC output of the inverter. The results of both sides were additionally compared between the two case studies: ungrounded and grounded systems. The real EMI testing results were also compared with the EMI/electromagnetic compatibility standard. The results confirm the effectiveness and benefits of system grounding, integrated with the proposed passive EMI filter.
Keywords: Electromagnetic Compatibility and Noise Suppression; Power Line Communications and Noise; Electrostatic Discharge in Electronics